Influences of the moving velocity and material property on frictionless contact problem of orthotropic materials indented by a moving punch - Zhou, Y.T.; Lee, K.Y.; Jang, Y.H. (Archives of Mechanics, 2013)
In analyzing the contact behavior of a material indented by a moving punch, of much importance are the contributions of the moving velocity and material property. The present paper develops a smoothly moving contact model for orthotropic materials indented by a rigid punch. Based on fundamental solutions of each eigenvalue case, the mixed boundary-value problem is reduced to a Cauchy type singular integral equation by applying the Galilean transformation and Fourier transform. Particularly, the exact solution of the obtained singular integral equation is presented, and closed-form expressions of the physical quantities are given for a flat punch and a cylindrical punch. Figures are plotted to show the influences of the moving velocity, material properties and other loadings on the contact behaviors and to reveal the surface damage mechanism, which may provide useful guidelines for material's designing and optimization.